Youth and ICTs: Moving with communities - Xavier, Asiimwe F. (Technical Centre for Agricultural and Rural Cooperation, 2012)
Young volunteers in Uganda are experimenting with solar-powered laptops and cell phones to present training videos to displaced nomadic communities.